مبخرة - Storage cabinet for the Noble Qur’an in Al-Rawdah | خزانة حفظ مصاحف الروضة الشريفة (2023)
Square area The diameter of the incense burner from the base = 46 cm, the height of the legs = 13 cm, the height of the bottom of the neck = 20 cm, the height of the bottom of the incense burner = 26 cm, the height of the handle = 6.5 cm | المساحة المربعة قطرالمبخرة من القاعدة = 46 سم ارتفاع الأرجل = 13سم ارتفاع قلة الرقبة =20سم ارتفاع قلة المبخرة=26سم ارتفاع المقبض= 6.5سم